Family Health Conversations Conducted by Telephone in Heart Failure Nursing Care: A Feasibility Study - Annelie K. Gusdal PhD; Karin Josefsson PhD; Eva T. Adolfsson PhD; Lene Martin PhD (SAGE Open Nursing, 2018)
Registered nurses (RNs) in heart failure (HF) nursing care have a key role in providing family support, which positively affects the outcome for the patient. Telephone interventions conducted by RNs have been reported to be successful in HF nursing care, but Family Health Conversations (FamHCs) involving the patient and the family, have not previously been tested. The purpose of the current study was to explore the experiences and feasibility of nurse-led FamHCs conducted by telephone with patients and their family caregivers. A single-group intervention study with a pretest–posttest design was conducted in three regional hospitals that had a nurse-led HF clinic. Five RNs, eight patients, and eight family caregivers participated. Three FamHCs were conducted by telephone with each family every 2 weeks. Qualitative and quantitative data were collected through semistructured interviews and questionnaires. FamHCs improved the nurse–family relationships and relationships within the families and provided RNs with new knowledge about the families. FamHCs conducted by telephone were considered to be feasible for both families and RNs, although RNs preferred fewer and shorter FamHCs. The RNs preferred meeting face-to-face with the families as nonverbal communication between the family members could be missed because of lack of visual input. On the other hand, RNs appreciated to focus entirely on the conversation without the need to perform illness-related routine checks. In conclusion, the advantages of FamHCs conducted by telephone outweighed the disadvantages. Visual contact, provided by video telephony, and a shorter version of the tested FamHC would facilitate the use in HF nursing care.